(untitled) (REMUNOM, 2025)
Introduction: Hypericum perforatum is a plant used as an inhibitor of serotonin reuptake and has been used in several European countries in the treatment of unipolar depression, one of the most prevalent mental disorders in the world. Objectives: To identify the therapeutic potential and effectiveness of the use of H. perforatum in the treatment of Major Depressive Disorder. Methods: This is an integrative review of a search conducted in the CAPES Portal Periódicos database. We included original articles from randomized controlled trials, published in the years 2000 to 2023, peer-reviewed, open access, in English, Portuguese and Spanish. Duplicate and non-human articles were excluded. In the search, 118 articles were identified and after the selection, eligibility and inclusion criteria, 9 articles were analyzed. Results: The reviewed studies compared the effect of H. perforatum with other antidepressants such as fluoxetine, paroxetine, sertraline and imipramine and with itself at different doses. Its dose of 500 to 1,800 mg/day and the duration of the intervention ranged from 6 to 84 weeks. Most of the studies reviewed have shown significant results in: decreased Depression scores with treatment with H. perforatum; superiority of the groups that received the herbal medicine in relation to the placebo group; efficacy in prophylaxis against remission and relapse. Conclusion: One can point to the effectiveness of H. perforatum in the treatment of Major Depressive Disorder, modulating, then, the brain neurotransmitters responsible for mood regulation. In addition, it has demonstrated a good safety profile and low incidence of side effects.